Unravelling the Causal Relationship between Endometriosis and the Risk for Developing Venous Thromboembolism: A Pooled Analysis - De Corte, Pauline; Milhoranca, Igor; Mechsner, Sylvia; Oberg, Anna Sara; Kurth, Tobias; Heinemann, Klaas (Thrombosis and Haemostasis, 2024)
To investigate the effect of endometriosis on venous thromboembolism (VTE) in oral contraceptive (OC) users. Pooled analysis on a harmonized dataset compromising international patient-centric cohort studies: INAS-VIPOS, INAS-SCORE, and INAS-FOCUS. Eleven European countries, the United States, and Canada. Individuals being newly prescribed an OC with or without an endometriosis and no VTE history.Detailed information was captured using self-administered questionnaires at baseline and every 6 to 12 months thereafter. Self-reported VTEs were medically validated and reviewed by an independent adjudication committee. Incidence rates (IRs) were calculated per 10,000 woman-years. The association of endometriosis on VTE was determined in a time-to-event analysis, calculating crude and adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) using stabilized inverse probability of treatment weighting (IPTW).A total of 22,072 women had an endometriosis diagnosis, and 91,056 women did not. Women with endometriosis contributed 78,751 woman-years during which 41 VTE events occurred (IR: 5.2/10,000, 95% CI: 3.7–7.1) compared to 127 VTEs during 310,501 woman-years in women without endometriosis (IR: 4.1/10,000, 95% CI: 3.4–4.9). The hazard ratio of VTE in women with endometriosis was 1.79 (95% CI: 1.24–2.57) using stabilized IPTW controlling for age, body mass index, smoking, education, age at menarche, and family history of VTE. Subgroup and sensitivity analyses showed similar results.These results highlight the importance of considering endometriosis as a potential factor contributing to VTE in women using OC; however, further research on the relationship between endometriosis and VTE is warranted.
Keywords: endometriosis; venous thromboembolism; oral contraceptive